Development of educational comic media in civics education to improve the literacy skills of students - Ma'lufah, Dina Zulva Ismi; Makmun, M. Ngali Zainal; Aisyah, Nurul (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2026)
This study addresses the limited use of innovative learning media in Civic Education (PKn) which affects students’ activeness and literacy skills in elementary schools. The research aims to develop educational comic media in PKn learning and to examine its feasibility and students’ responses in improving literacy skills. This study employed a Research and Development (R&D) method using the 4-D model, consisting of define, design, develop, and disseminate stages. The subjects of the study were fourth-grade students of SDNU Metro. Data were collected through interviews with teachers and the school principal, material expert and media expert validation questionnaires, and student response questionnaires. The findings indicate that the developed educational comic media is feasible to use based on material and media expert evaluations. Students' responses show a very positive category, particularly in increasing learning interest, reading motivation, and understanding of Pancasila values. Therefore, educational comic media can serve as an effective alternative learning medium to support literacy improvement in Civic Education learning at the elementary school level.